ANALISIS BEBAN KERJA TENAGA FILING REKAM MEDIS (STUDI KASUS RUMAH SAKIT IBU DAN ANAK BAHAGIA MAKASSAR) - Thabran Talib (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2018)
The initial obsevation in medical record of RSIA Bahagia Makassar is known the total number of personnel amounted to 10 people, the details of the admin 6 people, the data processing 4 people, while the filing part there is no power so that the workload analysis of medical record filing personnel. descriptive research method with observational analytic approach of accidental sampling population from daily average of 54 medical record files. Data collection with obesrvation using data analysis methods work load analysis. Based on the results of the effective working hours at RSIA Bahagia Makassar is 5.25 hours / day (18900 seconds) has been in accordance with the standard working hours of 5.25 hours / day (18900 seconds) and the completion time of all work in the filing section has been appropriate only only in the filing section there are no permanent personnel who handle the process in filing is still implemented by medical record personnel who also concurrently duty at the place of registration of patients. So the workforce in filing requires 1 person permanent personnel. The hospital should pay attention to the workforce and need to create the organizational structure of the medical record unit. With the organizational structure in the medical record unit it can clarify the responsibility, position, job description, thus it will form a permanent employee in the filing to maintain a workload within a certain time.